2021
DOI: 10.3390/cells10112966
|View full text |Cite
|
Sign up to set email alerts
|

Positive Regulation of Estrogen Receptor Alpha in Breast Tumorigenesis

Abstract: Estrogen receptor alpha (ERα, NR3A1) contributes through its expression in different tissues to a spectrum of physiological processes, including reproductive system development and physiology, bone mass maintenance, as well as cardiovascular and central nervous system functions. It is also one of the main drivers of tumorigenesis in breast and uterine cancer and can be targeted by several types of hormonal therapies. ERα is expressed in a subset of luminal cells corresponding to less than 10% of normal mammary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 200 publications
(296 reference statements)
2
26
0
Order By: Relevance
“…Regarding BC, its heterogeneous immunohistochemical profile is well established, with multiple possible targetable tumorigenic drivers, including ERα, ERBB2/HER2 and the progesterone receptor (PR, NR3C3). HER2 is a membrane receptor and its gene is frequently upregulated in BC, while PR is an ER target gene and a marker of better prognosis [22]. The receptor status has therapeutic and prognostic implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding BC, its heterogeneous immunohistochemical profile is well established, with multiple possible targetable tumorigenic drivers, including ERα, ERBB2/HER2 and the progesterone receptor (PR, NR3C3). HER2 is a membrane receptor and its gene is frequently upregulated in BC, while PR is an ER target gene and a marker of better prognosis [22]. The receptor status has therapeutic and prognostic implications.…”
Section: Discussionmentioning
confidence: 99%
“…ER+ and/or PR+ BC include almost two-thirds of total patients and they are suitable for the treatment with hormonal therapies, mostly aromatase inhibitors. ER positivity is usually maintained in the majority of recurrent BC [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The estrogen receptor α (ER-α) is heavily studied in cancers of various origin due to its role in cell proliferation and disease progression. ER-α plays a crucial role in driving breast and uterine cancers and is expressed in greater than 70% of ER + breast tumors ( Porras et al, 2021 ). In MCF-7 human breast cancer cells, Withaferin A treatment resulted in reduction in ER-α protein levels and pS2 levels, a product of ER-α regulated gene; this was attenuated in E2 presence ( Hahm et al, 2011b ).…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…In Palestine, Breast cancer was the third largest cause of cancer mortality in 2018 at 12% and a more than 135% rise in breast cancer cases is expected by 2040 (AlWaheidi 2019). Immunohistochemical analysis revealed that breast cancers that express the estrogen receptor, progesterone receptor or both respond well to hormone therapy (Aliwaini et al 2019;Porras et al 2021). Another important progress in breast cancer therapy was identifying and targeting the Her2 subtype of epidermal growth factor receptors (EGFR) which improved the outcome of Her2positive patients (Aliwaini et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…TNBCs are highly aggressive and resistant to conventional chemotherapy and are more common in individuals of African descent (Seachrist et al 2021). It is important to note that more than 70% of TNBCs overexpress genes implicated in metastasis and invasion as well as genes involved in proliferation and resistance to apoptosis including AKT, PI3K, RAS, and NF-Кb (Porras et al 2021). More importantly, mutations in p53 is reported to be one of the most common features of TNBCs and several studies indicate that these mutant p53 proteins enhance tumorigenesis and treatment resistance (O'Grady et al 2020).…”
Section: Introductionmentioning
confidence: 99%